Village Community Perceptions of the Economic Impact of the Merah Putih Cooperative - Hartono, Nanang Rudi; Dewi Wahyuni, Ervika; Veni Indriani, Novela (Journal of Scientific Research, Education, and Technology (JSRET), 2025)
This study explores the understanding and perceptions of the community of Rejotangan Village, Tulungagung Regency, regarding the economic impacts promised by the establishment of the Merah Putih Cooperative. The method used was descriptive qualitative with a participatory approach. Data were collected through in-depth interviews, participant observation, focus group discussions, and field documentation. The study findings indicate that most residents were familiar with the Merah Putih Cooperative through village announcements and special meetings, but detailed understanding varied. The community was generally optimistic that the cooperative could improve access to capital, income, and village food security, despite concerns about transparency and regulatory constraints. Factors determining community attitudes included trust in management, participation in deliberation processes, and local values ​​of mutual cooperation. These findings support previous literature that cooperatives can improve member welfare and strengthen the local economy, provided they are supported by cooperative literacy, institutional mentoring, and contextual policies. This article recommends strengthening cooperative socialization, manager training, and management transparency to ensure the Merah Putih Cooperative becomes an effective instrument for village economic empowerment